Nutritional intake of young Italian high-level soccer players: Under-reporting is the essential outcome - Caccialanza, R.; Cameletti, B.; Cavallaro, G. (Journal of Sports Science & Medicine, 2007)
It is recognized that much of the dietary data on adolescents and athletes is prone to reporting error, mostly through under-reporting. Nevertheless, in the majority of studies assessing the nutritional intake of young soccer players under-reporting has not been taken into consideration. The purpose of this study was to assess the dietary intake of a sample of young male Italian high-level soccer players on two time points to evaluate the degree of under- reporting. Seventy-five male high level soccer players (age range: 15-17 years) completed 4-day food records on two separate occasions (T0; T1, 3 months after T0). Under-reporting was assessed by the ratio of reported estimated energy intake (EEI) to estimated energy expenditure (EEE). Forty- three subjects, whose food records were judged accurate enough both at T0 and T1, were included in the data analysis (inclusion rate 57.3%). No significant weight changes were documented between T0 and T1 and in the two weeks preceding both T0 and T1. Reported mean daily energy intake was significantly lower than mean estimated daily energy expenditure both at T0 and T1 (p < 0.001). The average EEI/EEE ratio was 0.75 + 0.2 both at T0 and T1. It was < 80% in 27 subjects (62.8%) at T0 and in 23 (53.4%) at T1; it reached 50% in 4 subjects both at T0 and T1. The degree of under- reporting of the young soccer players was in line with the available data on this age group. This study emphasizes that under-reporting is a critical issue in the evaluation of young athletes dietary intake, which should be considered in the interpretation of data, particularly when energy inadequacies are reported. Further studies with uniformed methods are needed, in order to reduce the degree of under-reporting, obtain reliable data on the dietary intake of young soccer players and evaluate the efficacy of targeted nutrition education programs.